Solarscópio: equipamento para a filmagem e gravação do movimento aparente do sol - Silva, Claudinei Antônio (2016)
This dissertation aims to shoot the positions of the apparent motion of the Sun, through a Solarscope device developed with easily accessible materials and little cost, to understand the solar system and cyclic phenomena connected to it, such as translational motion and rotation of the Earth, the seasons, the summer solstice and winter solstice, autumn equinox and spring equinox , the geometry of the Earth as well as his inclination of 23° 27 ' 33 "to the plane perpendicular to the plane containing the ecliptic, and the inclination is one of the consequences that define the seasons on Earth. It was developed to provide middle and high school teachers, to promote the interest of their students in science and technology, helping them in the problematization of situations involving physical content that enable students to raise hypothesis in an attempt to explain the issues proposals on the movements of the Earth. Present methodological referrals through various teaching strategies, intensifying the possibilities of debates and discussions, facilitating the creation, analysis, formulation of concepts, developing ideas and choosing different paths for the referrals. Adopt the learning theory of Bruner, due the importance he gives to discovery method, based on the idea that knowledge of the structure of disciplines requires the use of the methodologies of science, by doing so, criticism of expository methodologies, considering, that learning science is done best through the involvement of students in the process of discovery and the use of scientific methodologies specific to each science.